2001
DOI: 10.1128/jcm.39.3.1134-1136.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Infection Caused by Aspergillus ustus , an Emerging Opportunistic Fungus in Immunosuppressed Patients

Abstract: We report a case of primary cutaneous infection by the emerging fungus Aspergillus ustus in an immunosuppressed patient after a domestic accident. The patient failed to respond to itraconazole and died before receiving a new treatment with amphotericin B. There have been eight other cases reported since 1973, and only two patients survived the infection. In vitro susceptibility testing of seven antifungal drugs showed that terbinafine and the new azole derivative UR-9825 were the most active against this fungu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 5 publications
2
22
0
Order By: Relevance
“…A. fumigatus, A. flavus, and A. terreus are the most common species. To date only 10 cases of infections caused by A. ustus have been reported (5,14,23). Four of the 10 patients suffered from IPA (2,11,23,25), and all of the patients died of fungal disease.…”
mentioning
confidence: 99%
“…A. fumigatus, A. flavus, and A. terreus are the most common species. To date only 10 cases of infections caused by A. ustus have been reported (5,14,23). Four of the 10 patients suffered from IPA (2,11,23,25), and all of the patients died of fungal disease.…”
mentioning
confidence: 99%
“…32 Penetrating trauma remains the major cause of primary cutaneous zygomycosis (Table 2). [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Other causes reported include elasticized bandages and wound dressings, 55 burns, 56 motor vehicle collision, 57 intravenous access, 58 and dog bite. 59 Our case report of primary cutaneous mucormycosis after a cat bite is a rare finding.…”
Section: Discussionmentioning
confidence: 99%
“…66 The higher overall mortality rate of 29.4% seen in the review of the literature was observed more frequently in patients with neutropenia (60.0%) and without surgical intervention (73.3%), and the survival rate was higher (35.3%) for cases utilizing both antifungal and surgical interventions. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The antifungal agent with the highest survival rate was amphotericin B and its formulations (58.8%). [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasingly greater focus on moulds as agents of infection in immunocompromised individuals, such as AIDS, cancer or transplant recipient patients undergoing hospital treatment (Gené et al 2001, White 2005, Kauffman 2006, Nucci and Anaissie 2006. The costs of using antifungal medicine have skyrocketed in many hospitals in recent years.…”
Section: Yearmentioning
confidence: 99%